Distorted perceptions of corporate harm in comparison to crime: a critical analysis of the Workers Compensation Act - Ostapovich, Sarah (My University, 2023)
This paper poses a critical analysis of the Worker’s Compensation Act, providing a foundation for the argument that crime is a social construct and therefore, is incapable of considering various aspects of corporate harm. Worker’s Compensation Board Appeals are examined to demonstrate the limits of the current state of the Worker’s Compensation Act, pointing specifically to harms that originate from workplace fatalities, long-term illnesses, and threats to mental health. The overall argument contends that we should move away from the narrow scope of the current definition of crime and seek a harm-based approach that allows for the consideration of multiple harms, which are often obscured by the criminal justice system.
Keywords: harm-based approach; critical criminology; criminal justice; Worker's Compensation Act